Advanced Computing and Systems for Security Volume Three - Chaki, Rituparna; Saeed, Khalid; Cortesi, Agostino; Chaki, Nabendu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents extended versions of papers originally presented and discussed at the 3rd International Doctoral Symposium on Applied Computation and Security Systems (ACSS 2016) held from August 12 to 14, 2016 in Kolkata, India. The symposium was jointly organized by the AGH University of Science & Technology, Cracow, Poland; Ca' Foscari University, Venice, Italy; and the University of Calcutta, India. The book is divided into two volumes, Volumes 3 and 4, and presents dissertation works in the areas of Image Processing, Biometrics-based Authentication, Soft Computing, Data Mining, Next-Generation Networking and Network Security, Remote Healthcare, Communications, Embedded Systems, Software Engineering and Service Engineering. The first two volumes of the book published the works presented at the ACSS 2015, which was held from May 23 to 25, 2015 in Kolkata, India.
A heuristic framework for priority based nurse scheduling -- All Spanning Tree Generation Algorithm using Divide-and-Conquer and its Application in Network Capacity Planning Process -- Circuit Synthesis of Maximum Clique Problem by using Quantum Walk -- Abort-free STM: A Non-Blocking Concurrency Control Approach using Software Transactional Memory -- Graph problems performance comparison using Intel Xeon and Intel Xeon-Phi -- A Novel Image Steganographic Scheme using 8x8 Sudoku Puzzle -- A Novel Image Steganographic Scheme using 8x8 Sudoku Puzzle -- Association Based Multi-Attribute Analysis to Construct Materialized View -- A new Method for Key Author Analysis in Research Professionals' Collaboration Network -- Single-shot Person Re-Identification by Spectral Matching of Symmetry-Driven Local Features -- Analysis of eavesdropping in QKD with Qutrit photon states -- Evaluating The Performance of A Chaos Based Partial Image Encryption Scheme -- Use of fusion biometric system based on keystroke dynamics and face image as a way to improve recognition system reliability.
Keywords: Computational intelligence; Signal processing; Data protection; Computational Intelligence; Signal, Speech and Image Processing; Data and Information Security